Cryo-EM structure of the calcium-sensing receptor complexed with the kokumi substance γ-glutamyl-valyl-glycine - Hiroki Yamaguchi; Seiji Kitajima; Hiroshi Suzuki; Shota Suzuki; Kouki Nishikawa; Akiko Kamegawa; Yoshinori Fujiyoshi; Kazutoshi Takahashi; Uno Tagami; Yutaka Maruyama; Motonaka Kuroda; Masayuki Sugiki (Scientific Reports)
Abstract Taste is a key element for food palatability and is strongly influenced by the five basic tastes and other taste sensations, such as fatty orosensation, and koku perception, which indicates taste complexity, mouthfulness and lastingness. This study focuses on the taste modifier γ-glutamyl-valyl-glycine (γ-EVG), a potent kokumi substance that enhances taste and koku perception by modulating the calcium-sensing receptor (CaSR). We used cryo-electron microscopy to determine the structure of the CaSR/γ-EVG complex at a resolution of 3.55 Å. Structural analysis revealed important interactions between γ-EVG and the CaSR, involving key residues, such as Pro39, Phe42, Arg66, Ser147, and Glu297. Mutagenesis experiments demonstrated the importance of these residues in peptide binding. Each γ-EVG residue contributed to its binding to the orthosteric ligand binding site of the CaSR. These findings elucidate the molecular basis of kokumi peptide recognition by the CaSR and contribute to a better understanding of positive allosteric modulators of the CaSR. In addition, this research provides valuable insights into the functionality of class C G-protein-coupled receptors in taste perception, potentially informing the development of new taste modifiers and advancing the field of food science.